Preventative Effect of Nafamostat Mesilate Infusion into the Main Pancreatic Duct on Post-ERCP Pancreatitis in a Porcine Model: Initial Pilot Study. Issue 4 (20th April 2020) - Park, Jin-Seok; Jeong, Seok; Kim, Joon Mee; Lee, Don Haeng
Abstract: Background and Aim: Post endoscopic retrograde cholangiopancreatography (post-ERCP) pancreatitis is not an uncommon adverse event but may not be avoidable. Various pharmacological and endoscopic techniques have been used to prevent post-ERCP pancreatitis (PEP), but most have been ineffective. The aim of this study was to evaluate the preventative effect of an intrapancreatic duct injection of nafamostat mesilate (NM) on PEP. Methods: This experimental study was conducted on 8 mini pigs. Animals were randomly allocated to a control group ( n = 4) and or a NM group ( n = 4). Pancreatitis was induced by infusing contrast medium into the main pancreatic duct by ERCP in all animals. After contrast medium injection, NM (50 mg/5 cc) was infused in the NM group and the same amount of 5% dextrose solution was infused in the control group. Twenty-four hours after endoscopic procedures, pancreatic inflammation, edema, vacuolization, necrosis and hemorrhage were evaluated histologically. Results: All animals survived until the end of the experiment. No peri-procedural technical difficulty or adverse event was encountered. Histologic examinations confirmed acute pancreatitis in all animals. In histologic acute pancreatitis scoring, no significant intergroup differences were observed between edema ( P = 0.134), leukocyte infiltration ( P = 0.356), vacuolization ( P = 1.000), or hemorrhage ( P = 0.071) scores. However, mean necrosis score was significantly lower in the NM group (1.0) than in controls (1.75, P = 0.024). Conclusion: NM injection into the intrapancreatic duct produced promising results with respect to the prevention of PEP development, especially regarding the prevention of necrosis.